IMPROVEMENT OF BEARING CAPACITY OF SHALLOW FOUNDATION ON SAND REINFORCED WITH POLYPROPYLENE FIBER - KHOSHNAW, RAWSHT MOHAMMED KUNI (Fırat Üniveristesi, 2023)
Kumlu zemin terimi, ağırlıklı olarak kumdan oluşan ancak az miktarda silt ve kil içeren zeminleri tanımlamak için kullanılmaktadır. Bu tür zeminler gevşek durumda olduklarında, özellikle depremler sırasında oturmalar yapmakta ve düşük kayma mukavemeti nedeniyle ağır yükleri taşıyamadıkları bilinmektedir. Bu nedenle, bu tür zeminleri inşaat için daha uygun hale getirmek için çeşitli yöntemler vardır. En yeni zemin iyileştirme tekniklerinden biri de, gerekli tür ve miktarda liflerin zemine eklenmesi, eşit olarak karıştırılması ve ardından uygun sıkılıkta yerleştirilmesidir. Düşük maliyetlerle yapılan bu zemin iyileştirmesi sayesinde, kayma mukavemeti ve taşıma kapasitesi artmakta ayrıca oturmalar azalmaktadır. Bu araştırmada, polipropilen elyafın bir zemin katkısı olarak kullanılabilirliği araştırılmış ve elyaf takviyeli zeminin mukavemet özellikleri incelenmiştir. Bu amaçla, dane boyutu analizi, Standart Proctor deneyi, büyük kesme kutusu deneyi, laboratuvar modelleme tankı deneyleri yapılmıştır. Ayrıca Plaxis 3D programı ile sonlu elemanlar yöntemi (FEM) ile yapılan deneyler doğrulanmıştır. Deneyler, zemine ağırlıkça sırasıyla yüzde (0, 0.5, 1 ve 1.5) PPF eklenmesi ile gerçekleştirilmiştir. Sığ temelin genişliği B olmak üzere (B=8cm) her karışımdaki zemin, temel altına (0.5B, 1B, 1.5B ve 2B) gibi dört farklı derinlikte sıkıştırılarak yerleştirilmiş ve taşıma gücü belirlenmiştir. Bu araştırmanın sonuçlarından, polipropilen elyafın optimum su içeriğini artırdığı ve maksimum kuru yoğunluğu azalttığı belirlenmiştir. Bu araştırma sonucunda optimum PPF içeriği değeri %1 olarak belirlenmiştir. Ayrıca, polipropilen elyaf takviyeli kum tabakasının optimum derinliği 1.5B olarak elde edilmiştir, derinliğin daha fazla artması dikkate değer bir taşıma gücü artışına sebep olmamaktadır. Plaxis 3D sonuçlarına göre, kumlu zemine PPF miktarı arttıkça taşıma gücü artmaktadır.

The term sandy soil describes soil composed predominantly of sand with only traces of clay and silt. Soil generally settles when heavy loads are applied, especially during earthquakes and it is obvious that weak soil has low shear strength and cannot support heavy loads. Because of this, there are several methods for making soils more suitable for construction. One of the most recent techniques includes adding the required type and number of fibers to the soil, mixing it equally in random directions, and then putting it in the appropriate location and it is a common method for improving weak soils. Soil reinforcement also results in increased shear strength, bearing capacity, and reduced costs. This research investigates the feasibility of using polypropylene fiber as a soil reinforcement and examines the strength properties of fiber-reinforced soil, for which various experiments are conducted including grain size analysis, Standard Proctor compression, big direct shear test, laboratory modeling tank tests, and finally the use of FEM like the Plaxis 3D program. The tests were performed with and without stabilization with the additions of (0, 0.5, 1, and 1.5) percent of PPF by mass of the soil sample, respectively. Each ratio mixes with sand under a shallow foundation at four different depths (0.5B, 1B, 1.5B, and 2B) once B refers to the width of the shallow foundation and is equal to 8 cm. This study demonstrates how polypropylene fiber alters the geotechnical characteristics of soils and when PPF is added to the sand, sand can be made more stable. PPF can increase optimum water content and reduce the maximum dry density and the best fiber content ratio in this research is 1% PPF content because reinforced sand has a good bearing capacity at this ratio due to it is cost-effectiveness. Also, the best depth of reinforced sand with polypropylene fiber is equal to 1.5B after that increasing reinforced soil depth is not important. According to the Plaxis 3D result, the bearing capacity value increases with increasing the amount of PPF in the sand but is always smaller than the experimental results.
Polipropilen elyaf takviyeli kum üzerinde sığ temelin taşıma kapasitesinin geliştirilmesi
Keywords: İnşaat Mühendisliği